Analysis of Risk Factors for Postoperative Delirium in Geriatric Patients at Skopje Macedonia Hospital: An Observational Study - Pekovska, Konstantina; Igor Mitevska (HM Publisher, 2024)
Introduction: Postoperative delirium (DPO) is a complication that often occurs in geriatric patients and can increase morbidity and mortality. Risk factors for DPO in geriatric patients are multifactorial, including advanced age, history of DPO, dementia, comorbidities, and use of certain medications. Methods: This study was carried out prospectively on 100 geriatric patients undergoing surgery at Skopje Macedonia Hospital. Patient data was collected using questionnaires, interviews, and physical examinations. DPO is defined using the confusion assessment method (CAM). Results: Of 100 patients, 20 (20%) experienced DPO. Risk factors for DPO identified in this study were elderly (OR = 2.5; 95% CI 1.2-5.1), history of DPO (OR = 3.0; 95% CI 1.4-6.2), dementia (OR = 4.0; 95% CI 1.8-8.8), and use of anticholinergic drugs (OR = 2.2; 95% CI 1.1-4.4). Conclusion: Elderly, history of DPO, dementia, and use of anticholinergic drugs are risk factors for DPO in geriatric patients. Efforts to prevent DPO in geriatric patients should focus on modifying these risk factors.